Da loucura à lucidez: discurso médico e alienação mental (São Luís: 1920-1940) - Damasceno, Pyetra Cutrim Lina (2015)
This present paper to understand psychiatric theories of the main theorical postulates hat developed on madness as well as understand the main principles of social medicine and eugenic political in the reconfiguration of urban spaces and the remodeling of the population's habits. We discuss the main restriction of actions of the spaces of the subjects considered crazy and how laws aimed at an organization of health care services, from the creation of alloys whose aim was to prevent the population of degeneration. The main problem revolves around the understanding of how these precepts arrived in São Luís and were used in the theory and practice of psychiatric Djalma Marques. The writings of Djalma Caldas Marques, in the "comments" of the journal "Pacotilha" are used as a place of diffusion of medical knowledge about mental illness and major medical discourse delivered in Brazil between the years 1920-1940.